Perbaikan Pakan Kambing Bligon Menggunakan Daun Ketela sebagai Suplemen (Feed Improvement of Bligon Goats Diet Using Cassava Leaf as Supplement) - Kustantinah (Kustantinah); Arif Nur Wibowo; Hari Hartadi (Faculty of Animal Science, Universitas Gadjah Mada, 2009)
Agricultural by-product, especially from cassava plants, can be found easily at all over Indonesia. Parts of cassava (Manihot esculenta Crantz) plant that can be used for animal feed are leaves, stem covering, tuber (in dry orwet condition, with or without skin). Cassava leaves cannot be used freely as animal feed, because of the persistence of anti-quality, i.e. Cyanide Acid (HCN) and tannin substance. Cassava leaves can be found easily in the dry season, whengenerally the presence of forage as ruminant’s diet is so limited. This research had to be done to observe potency of cassava leaves as supplement for Bligon goat’s diet. This research used 24 mature early pregnant Bligon goats. Thegoat divided into 3 treatments, those are : K as Control Diet (conventional diet which usually be given by the farmers); T1 or Treatment 1 (Control Diet+300 g cassava leaves); and T2 or Treatment 2 (Control Diet+260 g cassavaleaves+200 dried cassava tuber). The result showed that cassava leaves supplementation increased EE and TDN consumption. From total consumption, cassava leaves and dried cassava tuber increased DM, OM, CP, EE, and TDNdigestibility, but reduced CF digestibility. The effect of anti-coccidia didn’t appear optimally which shown by there was no significant differences of the amount of coccidian oocyste in the goat feces. However, the amount of coccidianoocyste in the feces reduced (1666.67 on the T1 and 2500 on the T2) as compare to those on the K (5000).(Key words: Bligon Goat, Cassava leaves, Feed Supplement, Coccidiostat)